Open Dialogue as a cultural practice - critical perspectives on power obstacles when teaching and enabling this approach in current psychiatry - von Peter, Sebastian; Eissing, Katrin; Saliger, Katharina (Frontiers in Psychology, 2023)
Building on both therapeutic and organizational principles, adopting Open Dialogue (OD) calls various routines of the current mental health system into question, resulting in potential obstacles with imple-mentation. This perspective paper aims to reflect on power relations as potential disruptive factors in enabling the OD approach in mental health care. Drawing on data from a small implementation study, followed by reflections from three perspectives, we conclude with a discussion exploring the potential of understanding OD as a fundamental human practice to reduce these power-related obstacles.